PENGARUH PENGGUNAAN TOKEN ECONOMIC TERHADAP KEMAMPUAN MENGENAL GRAFIK ANAK USIA 5-6 TAHUN DI RA AZZALIA KELURAHAN SIDOMILYO BARAT KECAMATAN TAMPAN PEKANBARU - Winarsih, Winarsih; Risma, Devi; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of tokeneconomic use on the ability to recognize graphs of children aged 5-6 years in RA Azzalia Sidomulyo Barat Tampan District Pekanbaru. This study uses an experimental method with the design of one group pre-test post-test design. The sample used in this study were 15 students. The data collection techniques used are observation. Techniques of data analysis using the t-test using SPSS 23. The research hypothesis is that there is an influence of the use of tokeneconomic on the ability to recognize graphics in children aged 5-6 years in RA Azzalia Village Sidomulyo Barat District Tampan Pekanbaru. Based on data analysis, it is known tcalculated = 7,660 > ttable = 2.145 with Sig. (2-tailed) = 0,000. Because Sig. <0.05, it can be concluded that there are differences in the ability to recognize graphics before and after being given the use of token economic. It can be interpreted that there is an effect of giving token economic use on the ability to recognize graphs of children aged 5-6 years in RA Azzalia Sidomulyo Barat Tampan District Pekanbaru.Keywords: Ability to Know Graphics, Use of Token Economic